2013
DOI: 10.1523/jneurosci.5497-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Memory Reactivation during Wakefulness and Sleep in Determining Which Memories Endure

Abstract: Consolidation makes it possible for memories of our daily experiences to be stored in an enduring way. We propose that memory consolidation depends on the covert reactivation of previously learned material both during sleep and wakefulness. Here we tested whether the operation of covert memory reactivation influences the fundamental selectivity of memory storage—of all the events we experience each day, which will be retained and which forgotten? We systematically manipulated the value of information learned b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
215
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(237 citation statements)
references
References 50 publications
(73 reference statements)
13
215
3
Order By: Relevance
“…This manipulation impaired trace eyeblink conditioning, a hippocampus-dependent learning task (Nokia et al 2012). Other studies in humans have shown that reactivation during SWS can enhance not only spatial memory but also procedural memories, suggesting that reintroduction of cues during sleep may reactivate other brain regions as well (Antony et al 2012;Oudiette et al 2013). These findings validate the hypothesis that NREM SWS is important for learning and memory (Girardeau et al 2009;Ego-Stengel and Wilson 2010).…”
Section: Sleep Enhances Memory Consolidationsupporting
confidence: 64%
See 1 more Smart Citation
“…This manipulation impaired trace eyeblink conditioning, a hippocampus-dependent learning task (Nokia et al 2012). Other studies in humans have shown that reactivation during SWS can enhance not only spatial memory but also procedural memories, suggesting that reintroduction of cues during sleep may reactivate other brain regions as well (Antony et al 2012;Oudiette et al 2013). These findings validate the hypothesis that NREM SWS is important for learning and memory (Girardeau et al 2009;Ego-Stengel and Wilson 2010).…”
Section: Sleep Enhances Memory Consolidationsupporting
confidence: 64%
“…In this seminal study, human subjects displayed improved memory of nonsense syllables when they slept during the period between learning and recall (Jenkins and Dallenbach 1924). Since this pivotal discovery, termed the "sleep effect," several other research groups have replicated the finding that memory benefits from sleep (Smith 2001;Born et al 2006;Gais et al 2007;Oudiette et al 2013;Stickgold and Walker 2013).…”
Section: Sleep Enhances Memory Consolidationmentioning
confidence: 99%
“…Thus, reward does not only support memory consolidation by increasing neuroplasticity in the hippocampus via dopamine release at encoding, but also by potentiating selective replay during sleep after encoding (Singer and Frank, 2009), recently confirmed also by optogenetic stimulation of mouse dopamine VTA-dorsal hippocampus pathway at encoding which enhanced spatial memory and increased reactivation of the stimulated neurons during sharp-wave ripples in post-encoding sleep (McNamara et al, 2014). In fact in humans, reward association or expectation has been shown to boost sleep-related gains in memory (Fischer and Born, 2009;Oudiette et al, 2013;Wilhelm et al, 2011;Igloi et al 2015). Reward circuits may play a role not only in selective memory consolidation during sleep, but also in the generation of dreams.…”
Section: Box 2: Role Of Sleep In the Consolidation And Generalizationmentioning
confidence: 86%
“…For instance, Cousins et al (2016) found that SWS cueing-related changes in neural activation were modulated by both SWS and subsequent REM. Oudiette et al (2013) reported that, in the absence of cueing, REM time was associated with declining memory accuracy for objectlocations. However, this association was abolished with cueing during SWS, thus cueing may have stabilised the memories and eliminated the processes involved in forgetting during REM sleep.…”
Section: Discussionmentioning
confidence: 99%